IMPLEMENTASI PЕMBЕLАJАRАN PAIKEM DАLАM PЕMBЕLАJАRАN BАHАЅА INDONESIA KELAS VIII SMP AL-IЅMАІLІУАH, BERINGIN, TAMBELANGAN, SAMPANG - Moh Ari Wibowo; Yusron; Jatim Desiyanto (Jurnal Cendekia Pendidikan, 2024)
Education is the process of acquiring knowledge, experience and behavior that is important in solving problems in life with values in society. Poor quality of teaching and learning is caused by ineffective interactions between students, teachers and the environment. PAIKEM learning is a solution to improve the quality of education and can be implemented in Indonesian language learning in class VIII of Al-Ismailiyah Middle School, Beringin, Tambelangan, Sampang. This research aims to determine the implementation of learning (PAIKEM) in the Indonesian language learning subject for Class VIII Al-Ismailiyah Middle School. In this research, researchers used the PTK classroom action research method. The research stage uses cycle II, cycle I includes the planning stage, action stage, evaluation stage, and reflection stage while cycle II basically repeats the stages of cycle I, but also makes new plans to correct deficiencies in the previous cycle. Data collection methods include interviews, observation, tests, documentation, data analysis. The results of this research can be stated that there was an increase in speech learning outcomes through the PAIKEM method for class VII students of Al-Ismailiyah Tambelangan Middle School from the first cycle which was completed by 4 students or 16% with the average result obtained being 61.03 and in the second cycle it increased 34 or 100% with an average value of 82.05